PENERAPAN AI DAN MACHINE LEARNING DALAM PENDIDIKAN ISLAM, SERTA ISU ETIKA DAN MORAL YANG TIMBUL DARI PENGGUNAANNYA - Sugiharto, Muhammad Samuel; Cahyadi, Ani; Hamdan, Hamdan (STIT Ibnu Rusyd Tanah Grogot, 2025)
The use of modern knowledge, such as Artificial Intelligence (AI), in Islamic education is becoming increasingly common. However, implementing AI requires adaptation, as students and teachers need to acquire more advanced skills to utilize this technology effectively. It is essential to understand the ethics and consequences of AI use in Islamic education to ensure its application is thoughtful and appropriate, with full awareness of potential risks. AI can also support discovery-based learning and create a learning environment that encourages exploration and innovation. AI’s ability to analyze data and learn from experience is valuable for enhancing accuracy and personalization in education. Despite AI's numerous positive potentials, there are aspects that require careful consideration and further study. Therefore, this research aims to explore AI usage in Islamic education through a literature review that combines qualitative methods and library research. This literature review uses secondary data from various relevant sources on the research topic. While AI offers significant potential benefits in Islamic education, there is also a risk of misuse, necessitating comprehensive analysis and holistic solutions.